ASSESSMENT OF MICROALBUMINURIA IN ESSENTIAL HYPERTENSIVES AND ITS RESPONSE TO ANGIOTENSIN-CONVERTING ENZYME INHIBITOR THERAPY - Sharma, Preeti; Kumar, Pradeep; Sharma, Rachna; Gk, Tripathi; Gupta, Gaurav (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Objective is to study the prevalence of microalbuminuria among patients suffering from essential hypertension and also to evaluate the response of microalbuminuria to angiotensin-converting enzyme (ACE) inhibitors therapy. Methods: The study conducted at Santosh Medical College and Hospital, Ghaziabad, on 300 patients with essential hypertension. After attaining baseline parameters in all patients, those newly diagnosed essential hypertensives with microalbuminuria not on any treatment were started on an ACE inhibitor (ramipril), for 8 weeks, after which all parameters were reassessed and comparison and statistical analysis were done to establish the prevalence of microalbuminuria and its response to therapy. Results: In our study, mean microalbuminuria excretion was 101.79 mcg/mg creatinine at the beginning of the study and 80.20 mcg/mg creatinine after 8 weeks of ACE inhibitor therapy, with 21.2% fall rate. Conclusion: Microalbuminuria is an independent risk factor for the development or worsening of hypertensive nephropathy and endothelial dysfunction, thereby increasing the risk of micro- and macro-vascular complications. Keywords: Microalbuminuria, Essential hypertension, Angiotensin-converting enzyme inhibitor therapy.